Anatomical and Physiological Appearances of Seagrass (Enhalus acoroides) in The Polluted Environment of Kayeli Bay, Maluku Province - Natsir, Nur Alim; T, Rosmawati; AF, Asyik Nur Allifah (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Pollution in Kayeli Bay is from the Marlosso and Nametek rivers. This area forces full adaptation of biota, including the seagrass Enhalus acoroides. This study aimed to compare changes in the anatomical structure and physiological response of the seagrass Enhalus acoroides. The preparation method uses a modification of the Ruzin method. Measurements are made using a microscope equipped with a micrometer and a spectrophotometer. The results showed that the thickness of the root epidermis and endodermis in the Marlosso area was 5.77 μm and 2.3 μm; and in Nametek, epidermis 5.58 μm and endodermis 1.54 μm. The epidermis and endodermis of the Marlosso rhizomes are 9.98 μm and 3.5 μm. Nametek rhizomes are 6.62 μm and 3 μm. The leaf tissue in Marlosso, namely the adaxial and abaxial cuticle, is 0.57 μm, the adaxial and abaxial epidermis is 2.84 μm and 2.78 μm, the thickness of the epidermis and cuticle is 10.2 μm and 1.81 μm. Nametek Waters are 0.45 μm and 0.54 μm, and the adaxial and abaxial epidermis are 1.62 μm and 2.29 μm. It was concluded that there was thickening of the cell walls in all tissues in the Marlosso River, and showed lower chlorophyll content compared to Nametek.